Modeling Two-Phase System in Complex Domains Based on Phase-Field Approach with Interfacial Correction (Communications in Computational Physics, 2024)
We introduce a novel phase-field model designed for ternary Cahn-Hilliard(CH) dynamics, incorporating contact angle boundary conditions within complex domains. In this model, we utilize a fixed phase field variable to accurately representintricate domains within the ternary CH system. Simultaneously, the remaining twophase field variables are employed to simulate CH dynamics effectively. The contactangle term is derived from Young’s equality and the hyperbolic tangent profile of theequilibrium interface. To ensure compliance with the hyperbolic tangent property atthe interface, a fidelity term is incorporated into the original CH model. This additionreduces mass loss for each phase and improves the accuracy of the contact angle effect.Moreover, we implement a finite difference scheme along with a nonlinear multigridmethod to solve the corrected ternary CH model. A series of numerical experimentsis conducted in both two- and three-dimensional spaces to demonstrate the efficiencyand robustness of the proposed model.